The relationship of tobacco, alcohol, and betel quid with the formation of oral potentially malignant disorders: A community-based study from northeastern thailand - Prangtip Worakhajit (2022)
This study’s objective was to describe the relationship between the main risk factors for oral cancer, including tobacco (in the form of cigarettes, smokeless tobacco (SLT), secondhand smoking (SS)), alcohol, and betel quid (BQ), and the occurrence of oral potentially malignant disorders (OPMDs). A community-based case-control study was conducted with a population of 1448 adults aged 40 years or above in northeastern Thailand. Patients aged 60 years or above (OR 1.79, p < 0.001) and female patients (OR 2.17, p < 0.001) had a significant chance of having OPMDs. Our multivariate analysis showed that the most potent risk factor for OPMDs occurrence was betel quid (BQ) (adjusted OR 4.65, p < 0.001), followed by alcohol (OR 3.40, p < 0.001). Even former users were at risk of developing OPMDs. The synergistic effect between these main risk factors was significantly shown in the group exposed to SLT, SS, BQ, and alcohol. The most potent synergistic effect was found in the group exposed to SLT, BQ and alcohol with the OR = 20.96.